Pregnancy-Related Hormones Increase UGT1A1-Mediated Labetalol Metabolism in Human Hepatocytes - Khatri, Raju; Fallon, John K.; Sykes, Craig; Kulick, Natasha; Rementer, Rebecca J. B.; Miner, Taryn A.; Schauer, Amanda P.; Kashuba, Angela D. M.; Boggess, Kim A.; Brouwer, Kim L. R.; Smith, Philip C.; Lee, Craig R. (Frontiers in Pharmacology, 2021)
Pregnancy-related hormones (PRH) are recognized as important regulators of hepatic cytochrome P450 enzyme expression and function. However, the impact of PRH on the hepatic expression and function of uridine diphosphate glucuronosyltransferases (UGTs) remains unclear. Using primary human hepatocytes, we evaluated the effect of PRH exposure on mRNA levels and protein concentrations of UGT1A1, UGT2B7, and other key UGT enzymes, and on the metabolism of labetalol (a UGT1A1 and UGT2B7 substrate commonly prescribed to treat hypertensive disorders of pregnancy). Sandwich-cultured human hepatocytes (SCHH) from female donors were exposed to the PRH estradiol, estriol, estetrol, progesterone, and cortisol individually or in combination. We quantified protein concentrations of UGT1A1, UGT2B7, and four additional UGT1A isoforms in SCHH membrane fractions and evaluated the metabolism of labetalol to its glucuronide metabolites in SCHH. PRH exposure increased mRNA levels and protein concentrations of UGT1A1 and UGT1A4 in SCHH. PRH exposure also significantly increased labetalol metabolism to its UGT1A1-derived glucuronide metabolite in a concentration-dependent manner, which positively correlated with PRH-induced changes in UGT1A1 protein concentrations. In contrast, PRH did not alter UGT2B7 mRNA levels or protein concentrations in SCHH, and formation of the UGT2B7-derived labetalol glucuronide metabolite was decreased following PRH exposure. Our findings demonstrate that PRH alter expression and function of UGT proteins in an isoform-specific manner and increase UGT1A1-mediated labetalol metabolism in human hepatocytes by inducing UGT1A1 protein concentrations. These results provide mechanistic insight into the increases in labetalol clearance observed in pregnant individuals.